1989
DOI: 10.1136/oem.46.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and health studies of farm workers in Swedish swine confinement buildings.

Abstract: The relation between the health of workers and the environment in swine confinement buildings was investigated in a study of 57 workers on 30 swine farms in southern Sweden and 55 matched controls. Swine workers reported significantly higher frequencies of respiratory symptoms, more frequent colds and absence due to chest illness, and a history of pneumonia. The increased frequency of symptoms of respiratory disease was related to the number of years and per cent of the day spent working with swine. Symptoms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
275
6
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(304 citation statements)
references
References 24 publications
20
275
6
3
Order By: Relevance
“…This has been confirmed in several studies from northern Europe, Canada, and the USA [2±8]. The dust from confinement buildings has strong biological properties and causes severe bronchial inflammation [9,10] and work in confinement buildings is associated with a cross-shift decline in forced expiratory volume in one second (FEV1) [7,11,12]. Several cross-sectional studies have suggested that pig farmers develop bronchial hyperresponsiveness and that this is related to symptoms and airway obstruction [8, 13±16].…”
mentioning
confidence: 63%
“…This has been confirmed in several studies from northern Europe, Canada, and the USA [2±8]. The dust from confinement buildings has strong biological properties and causes severe bronchial inflammation [9,10] and work in confinement buildings is associated with a cross-shift decline in forced expiratory volume in one second (FEV1) [7,11,12]. Several cross-sectional studies have suggested that pig farmers develop bronchial hyperresponsiveness and that this is related to symptoms and airway obstruction [8, 13±16].…”
mentioning
confidence: 63%
“…monocytes, dendritic cells and neutrophils [11]. In addition, TLR4 signalling contributes to the development and progression of chronic respiratory disease including asthma [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic airway inflammation possibly is exacerbated by exposure to microbes and their products in bioaerosols. For instance endotoxin, a highly toxigenic, bacterial lipopolysaccharide component of gram-negative bacterial cell walls, has been associated with reduced lung function in swine farmers (Donham et al 1989b;Vogelzang et al 1998). Correlations between biotic and abiotic exposures and respiratory disease have been the focus of many aerosol studies and have led to the establishment of dust, gas, and endotoxin exposure levels (Crook et al 1991;Seedorf et al 1998;Predicala et al 755 756 M. RODRÍGUEZ DE EVGRAFOV ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrated animal feeding operation (CAFO) employment is associated with increased incidences of multiple respiratory disorders, including asthma, chronic bronchitis, organic dust toxic syndrome, chronic obstructive pulmonary disease, rhinitis, hypersensitivity, hydrogen sulfide and carbon dioxide poisoning, and acute lower respiratory tract inflammation (Donham et al 1989a;Crook et al 1991;Schenker et al 1998;Von Essen and Donham 1999;Cole et al 2000;Sprince et al 2000;Danuser et al 2001;Radon et al 2001Radon et al , 2002Monso et al 2003Monso et al , 2004. Chronic airway inflammation possibly is exacerbated by exposure to microbes and their products in bioaerosols.…”
Section: Introductionmentioning
confidence: 99%